Prevalence of hippocampal enlarged perivascular spaces in a sample of patients with hypertension and their relation with vascular risk factors and cognitive function - Jiménez-Balado, Joan; Riba-Llena, Iolanda; Garde, Edurne; Valor, Marta; Gutiérrez, Belen; Pujadas, Francesc; Delgado, Pilar (Journal of neurology, neurosurgery and psychiatry, 2018)
ObjectivesThe clinical importance of hippocampal enlarged perivascular spaces (H-EPVS) remains uncertain. We aimed to study their association with vascular risk factors, cognitive function and mild cognitive impairment (MCI).MethodsData were obtained from the ISSYS (Investigating Silent Strokes in hYpertensives, a magnetic resonance imaging Study) cohort, which is a prospective study of patients with hypertension aged 50–70 with no prior stroke or dementia. Participants were clinically evaluated and underwent a cognitive screening test, Dementia Rating Scale-2, which includes five cognitive subscales (attention, initiation/perseveration, conceptualisation, construction and memory). Besides, they were diagnosed with MCI or normal ageing following standard criteria. H-EPVS were manually counted on brain MRI according to a previous scale and defined as extensive when H-EPVS count was ≥7 (upper quartile). Multivariate models were created to study the relationship between H-EPVS, vascular risk factors and cognitive function.Results723 patients were included; the median age was 64 (59–67) and 51% were male. Seventy-two patients (10%) were diagnosed with MCI and 612 (84.6%) had at least 1 H-EPVS. Older age (OR per year=1.04, 95% CI 1.01 to 1.08) and poor blood pressure treatment compliance (OR=1.50, 95% CI 1.07 to 2.11) were independently associated with extensive H-EPVS. Regarding cognitive function, H-EPVS were independently and inversely correlated with verbal reasoning (β=−0.021, 95% CI −0.038 to −0.003). No association was found between H-EPVS and MCI.ConclusionsH-EPVS are a frequent finding in patients with hypertension and are associated with ageing and poor hypertension treatment compliance. Besides, H-EPVS are associated with worse verbal reasoning function.